2015
DOI: 10.1007/s12031-015-0589-3
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Binding Protein-2 Promotes Adhesion of Endothelial Progenitor Cells to Endothelial Cells via Integrin α5β1

Abstract: The contribution of endothelial progenitor cells (EPCs) to new vessel formation has been studied in different physiological and pathological conditions for decades. As previously suggested, insulin-like growth factor binding protein-2 (IGFBP-2) may interact with integrins and promote cell migration. However, the role of IGFBP-2 in regulation of EPC functions remains largely unknown. In this present study, we found that overexpression of IGFBP-2 in human umbilical vein endothelial cells (HUVECs) promoted EPC-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Student's t test was applied. [45][46][47][48][49][50][51] Moreover, we discovered that EPC-secreted paracrine factors activated their respective receptors and downstream signaling molecules in ECs. 26,42,43 There are four families of axon guidance molecules (slit, semaphorin, NTN, and ephrin) and their receptors (the UNC5, neogenin, plexin, roundabout, and Eph).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Student's t test was applied. [45][46][47][48][49][50][51] Moreover, we discovered that EPC-secreted paracrine factors activated their respective receptors and downstream signaling molecules in ECs. 26,42,43 There are four families of axon guidance molecules (slit, semaphorin, NTN, and ephrin) and their receptors (the UNC5, neogenin, plexin, roundabout, and Eph).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, we found that NTN4 stimulated the secretion of paracrine angiogenic factors, such as EG-VEGF, VEGF-C, endothelin-1, IGFBP-2, pentraxin-3, PDGF-AA, and THBS-2; it was capable of directly or indirectly promoting EPC homing or EC sprouting. [45][46][47][48][49][50][51] Moreover, we discovered that EPC-secreted paracrine factors activated their respective receptors and downstream signaling molecules in ECs. Therefore, NTN4's strong effects with regard to promoting neovascularization in vivo might be the result of continuous synergistic effects with various factors.…”
Section: Discussionmentioning
confidence: 94%
“…IGFBP2 in circulation can stimulate or inhibit the growthpromoting effects of the IGFs (Binkert et al, 1992;Bourner et al, 1992). However, IGFBP2 has an RGD site that can activate integrin signaling independently of IGF receptors (Feng et al, 2015), and modulates the expansion and survival of hematopoietic stem cells (Huynh et al, 2011). Whether IGFBP2 and IGFBP3 function in an IGF-dependent or -independent manner in an in vivo context during salivary gland development and how they regulate epithelial progenitor cells remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IGFBP2 was shown to bind and activate αVβ3 integrin on ECs and tumour cells, leading to the expression of VEGF via the PI3K pathway (Das et al , ). Furthermore, IGFBP2 promoted EC–EPC interactions and cellular motility through binding with its tripeptide Arg‐Gly‐Asp (RGD) domain to α5β1 integrin (Wang et al , ; Feng et al , ). However, in these studies the relative contributions of autocrine/paracrine versus intracellular functions of IGFBP2 were not clearly addressed.…”
Section: Blood Brothersmentioning
confidence: 99%